THEORETICAL PROBLEMS OF CENTRALIZATION AND DECENTRALIZATION OF LOCAL BUDGETS - Muminov, Nozim (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the problem of centralization and decentralization of the budget. Budget decentralization is interconnected with the processes of geographical decentralization and decentralization of the system of administrative decision-making. Decentralization of the system of making and executing administrative decisions implies a wider delegation of authority to local divisions of the central executive authority. The article also states that the main goal of decentralization is to create a closer relationship between the control system and the population, and this requires strengthening the financial system of local governments. The task of decentralization is to provide the regions and local governments with certain powers in the field of taxation and expenditure of funds, as well as the ability to independently determine the parameters and structure of the budget expenditures. The article substantiates the advantages and disadvantages of budget centralization. Attempts were made to cover all arguments for and against decentralization.